Linking institutional and ecological provisions for wastewater treatment discharge in a rural municipality, Eastern Cape, South Africa - Muller, Matthew Justin (Rhodes University, Faculty of Science, Institute for Water Research, 2013)
The Green Drop Certification Programme, launched in 2008 alongside the Blue Drop Certification Programme, aims to provide the Department of Water Affairs with a national overview of how municipalities and their individual wastewater treatment works (WWTW) are complying with licence conditions set by the National Water Act (NWA) (No. 36 of 1998; DWAF 1998) and the Water Services Act (No. 108 of 1997; DWAF 1998). By publishing the results of each municipality's performance, the programme aims to ensure continuous improvement in the wastewater treatment sector through public pressure. The programme has been identified by this project as a necessary linking tool between the NWA and the Water Services Act to ensure protection and sustainable use of South Africa's natural water resources. It does this through assisting municipalities to improve their wastewater treatment operations which in theory will lead to discharged effluent that is compliant with discharge licence conditions. These discharge licences form part of the NWA's enforcement tool of Source Directed Controls (SDC) which help a water resource meet the ecological goals set for it as part of Resource Directed Measures (RDM). The link between meeting the required SDC and achieving the RDM goals has never been empirically tested. This project aimed to determine the present ecological condition of the Uie River, a tributary of the Sundays River which the Sundays River Valley Municipality (SRVM) discharges its domestic effluent into. It then determined whether the SRVM's WWTW was complying with the General Standard licence conditions and what the impact of the effluent on the river was through the analysis of monthly biomonitoring, water chemistry and habitat data. Lastly, the project examined the effectiveness of the Green Drop Certification Programme in bringing about change in the SRVM's wastewater treatment sector, which previously achieved a Green Drop score of 5.6 percent. It wanted to examine the underlying assumption that a WWTW which improves its Green Drop score will be discharging a better quality effluent that will help a water resource meets the RDM goals set for it. The Kirkwood WWTW did not have a discharge licence at the time of assessment and was thus assessed under the General Standard licence conditions. It was found that the Kirkwood WWTW was not complying with the General Standard discharge licence conditions in the Uie River. This was having a negative impact on the river health, mainly through high concentrations of Total Inorganic Nitrogen (TIN-N), orthophosphate and turbidity. The SRVM should see an improvement in its Green Drop score for the Kirkwood WWTW. However, the municipality showed no implementation of necessary programmes. Implementation of these programmes would help the SRVM meet the General Standard licence conditions (part of SDC) which would help the Uie River meet the RDM goals set for it.
Keywords: Sewage disposal plants -- South Africa -- Sundays Estuary (Eastern Cape); Sewage disposal -- Law and legislation -- South Africa; Sewage -- Environmental aspects -- South Africa; Water-supply -- South Africa -- Management; Sewage disposal in rivers, lakes, etc. -- South Africa -- Sundays Estuary (Eastern Cape); Rivers -- Environmental aspects -- South Africa -- Sundays Estuary (Eastern Cape); Rivers -- Regulation -- South Africa